Reconfigured Cyanogenic Glucoside Biosynthesis in Eucalyptus cladocalyx Involves a Cytochrome P450 CYP706C55. Issue 3 (8th October 2018) - Hansen, Cecilie Cetti; Sørensen, Mette; Veiga, Thiago A.M.; Zibrandtsen, Juliane F.S.; Heskes, Allison M.; Olsen, Carl Erik; Boughton, Berin A.; Møller, Birger Lindberg; Neilson, Elizabeth H.J.
Abstract : Cyanogenic glucoside biosynthesis in Eucalyptus cladocalyx requires an additional pathway step, involving three CYPs from the CYP79, CYP706, and CYP71 families, and a glucosyltransferase UGT85. Abstract: Cyanogenic glucosides are a class of specialized metabolites widespread in the plant kingdom. Cyanogenic glucosides are α-hydroxynitriles, and their hydrolysis releases toxic hydrogen cyanide, providing an effective chemical defense against herbivores. Eucalyptus cladocalyx is a cyanogenic tree, allocating up to 20% of leaf nitrogen to the biosynthesis of the cyanogenic monoglucoside, prunasin. Here, mass spectrometry analyses of E. cladocalyx tissues revealed spatial and ontogenetic variations in prunasin content, as well as the presence of the cyanogenic diglucoside amygdalin in flower buds and flowers. The identification and biochemical characterization of the prunasin biosynthetic enzymes revealed a unique enzyme configuration for prunasin production in E. cladocalyx . This result indicates that a multifunctional cytochrome P450 (CYP), CYP79A125, catalyzes the initial conversion of l -phenylalanine into its corresponding aldoxime, phenylacetaldoxime; a function consistent with other members of the CYP79 family. In contrast to the single multifunctional CYP known from other plant species, the conversion of phenylacetaldoxime to the α-hydroxynitrile, mandelonitrile, is catalyzed by two distinct CYPs. CYP706C55 catalyzes the dehydration of phenylacetaldoxime, an unusual CYP reaction. The resulting phenylacetonitrile is subsequently hydroxylatedby CYP71B103 to form mandelonitrile. The final glucosylation step to yield prunasin is catalyzed by a UDP-glucosyltransferase, UGT85A59. Members of the CYP706 family have not been reported previously to participate in the biosynthesis of cyanogenic glucosides, and the pathway structure in E. cladocalyx represents an example of convergent evolution in the biosynthesis of cyanogenic glucosides in plants.